Warm up - Leach, Sara, 1971- (Orca limelights., 2014)
Jasmine used to love dance, but it's hard to remember when her dance team is falling apart. During one particularly rough practice, she channels her anger into her moves, and surprises everyone with how well she dances. But the team is still at odds, and it's up to Jasmine to figure out how to get them to work together and celebrate the joy of dance.